Angioedema secondary to angiotensin converting enzyme inhibitors - Thiruventhiran, T.; Ho, Bee Kiau (Faculty of Medicine, University of Malaya, 1999)
Angioedema due to whatever cause is potentially life threatening, especially if it involves the head and neck region. Patients at risk need to be identified and precautionary measures are necessary. The use of Angiotensin Converting Enzyme Inhibitors (ACEIS) has been associated with angioedema of the face and tongue. Its widespread use has resulted in an increased awareness of this rare but important complication. We report here a case of angioedema secondary to ACEIS developing a few months after initiation of therapy and discuss its clinical importance.